The Impact of Dividend Policy, Capital Structure, and Company Growth on Financial Performance in Manufacturing Companies Listed on the IDX - Judijanto, Loso; Setiawan, Puguh (West Science Accounting and Finance, 2025)
This study examines the effect of dividend policy, capital structure, and company growth on the financial performance of manufacturing companies listed on the Indonesia Stock Exchange (IDX). Using a quantitative approach, data were collected from 110 samples and analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results reveal that all three factors—dividend policy, capital structure, and company growth—positively and significantly influence financial performance. Capital structure demonstrated the strongest impact, highlighting its critical role in optimizing financial outcomes. These findings emphasize the importance of strategic financial management in manufacturing firms to sustain growth and enhance profitability.